2002
DOI: 10.1046/j.1365-313x.2002.01330.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel, two‐component system for cell lethality and its use in engineering nuclear male‐sterility in plants

Abstract: SummaryAblation of cells by the controlled expression of a lethal gene can be used to engineer plant traits such as male sterility and disease resistance. However, it may not be possible to achieve suf®cient speci®city of expression to prevent secondary effects in non-targeted tissues. In this paper we demonstrate that the extracellular ribonuclease, barnase, can be engineered into two complementary fragments, allowing overlapping promoter speci®city to be used to enhance targeting speci®city. Using a transien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 61 publications
(66 reference statements)
1
38
0
1
Order By: Relevance
“…Another approach to address this leaky expression is to take advantage of the reconstitutable function of truncated, complementary Barnase peptide fragments. For example, when truncated Barnase gene fragments driven by diVerent promoters sharing overlapping Xoral-speciWc activity are simultaneously expressed in tomato plants, the truncated, non-functional Barnase peptides are biochemically reconstituted in Xoral tissues as functional Barnase proteins that quickly ablate their resident cells or tissues through the degradation of cellular RNAs (Burgess et al 2002). This is a sophisticated tactic, but whether it is feasible and practical for crop species remains to be demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Another approach to address this leaky expression is to take advantage of the reconstitutable function of truncated, complementary Barnase peptide fragments. For example, when truncated Barnase gene fragments driven by diVerent promoters sharing overlapping Xoral-speciWc activity are simultaneously expressed in tomato plants, the truncated, non-functional Barnase peptides are biochemically reconstituted in Xoral tissues as functional Barnase proteins that quickly ablate their resident cells or tissues through the degradation of cellular RNAs (Burgess et al 2002). This is a sophisticated tactic, but whether it is feasible and practical for crop species remains to be demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Anthers in Arabidopsis thaliana have a four-lobed structure, each containing a sporangium in which, early in development, two cell lines differentiate: (1) the germ line is a mass of cells that through sporogenesis and gametogenesis produces the male gametophytes and (2) the surrounding sporophytic tissues differentiate into four cell layers named from outside to inside, the epidermis, the endothecium, the middle cell layer, and the tapetum (Sanders et al, 1999;Ma, 2005). Several studies have shown that the surrounding four cell layers are crucial for the development of microsporocytes into mature pollen (Mariani et al, 1990;Burgess et al, 2002). Thus, mature anthers are highly organized structures.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that barnase toxicity can vary widely depending on species and growth environment. It also supports the need for steps to reduce barnase toxicity due to misexpression, which could include the use of spacers (Jagannath et al 2001), separation of subunits among plants following crossing (Burgess et al 2002;Bihao et al 2012), or attenuated versions of the protein (Zhang et al 2012).…”
Section: Discussionmentioning
confidence: 78%